The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1161/circheartfailure.109.862383
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Wave Analysis of the Aortic Pressure Waveform in Severe Left Ventricular Systolic Dysfunction

Abstract: Background-The effect of moderate left ventricular systolic dysfunction (LVSD) on ventricular/vascular coupling and the aortic pressure waveform (AoPW) has been well described, but the effect of severe LVSD has not. Methods and Results-We used noninvasive, high-fidelity tonometry of the radial artery and a mathematical transfer function to generate the AoPW in 25 treated patients with LVSD (mean LV ejection fraction, 24Ϯ8.8%; range, 11% to 40%; 21 patients Ͻ30%). Pulse wave analysis of the AoPW was used to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(84 citation statements)
references
References 50 publications
5
77
0
2
Order By: Relevance
“…Therefore, in these patients arterial wave reflections induce a negative influence on flow rather than a positive influence on pressure. 27) This deleterious effect of wave reflections has been described in patients with LVSD by Denardo, et al 28) They reported a decrease in all components of central and peripheral blood pressure compared with normal subjects with a reduction in ED, in reflected wave amplitude, and in Ew of LV effort. It must be pointed out that these authors considered patients with severe LV impairment (mean LVEF = 24%) to be comparable to our LVSD patient subgroup of 12 patients with more compromised LV function (mean LVEF = 29%).…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, in these patients arterial wave reflections induce a negative influence on flow rather than a positive influence on pressure. 27) This deleterious effect of wave reflections has been described in patients with LVSD by Denardo, et al 28) They reported a decrease in all components of central and peripheral blood pressure compared with normal subjects with a reduction in ED, in reflected wave amplitude, and in Ew of LV effort. It must be pointed out that these authors considered patients with severe LV impairment (mean LVEF = 24%) to be comparable to our LVSD patient subgroup of 12 patients with more compromised LV function (mean LVEF = 29%).…”
Section: Discussionmentioning
confidence: 76%
“…The complete pulse pressure waveform is known to provide valuable information for diagnostics and therapy of cardiovascular diseases such as arteriosclerosis, hypertension and left ventricular systolic dysfunction [37][38][39][40] . Many hemodynamic parameters such as arterial index, upstroke time, stroke volume variation and cardiac output can be directly calculated or estimated in real time from the pressure waveforms 41,42 .…”
Section: Articlementioning
confidence: 99%
“…9 In the presence of LV systolic dysfunction, the load imposed by the reflected wave may be predominantly associated with a pronounced decrease and early cessation of flow 21 and shortening of the ejection period. 22 In contrast to early systole, when systolic pressure and "diastolic" geometry (thin wall and large cavity) occur, myocardial fiber shortening and ejection of blood determine a progressive change in LV geometry, which causes a decrease in myocardial stress (despite rising pressure) during mid-to-late systole, such that wall stress tends to reach its lowest ejection-phase value in end systole. 19 This sequence of events appears to be ideal for the myocardium to handle the additional load imposed by wave reflections and may be compromised in ventricles with depressed ejection fraction.…”
Section: Resting Versus Provoked Loadmentioning
confidence: 99%